Linear and nonlinear intraday causalities in response to U.S. macroeconomic news announcements: Evidence from Central Europe - Henryk Gurgul; Tomasz Wójtowicz; Łukasz Lach (Managerial Economics)
The main goal of this paper is to analyze the information flow on and between the three stock markets in Frankfurt, Vienna, and Warsaw. These markets are rather different, since the capitalization of the Frankfurt Stock Exchange (FSE) is about ten times greater than that of the Warsaw Stock Exchange (WSE) and the Vienna Stock Exchange (VSE)1. There are, however, many facts that suggest that the FSE, VSE, and WSE may be strongly interrelated. First, the VSE and WSE are similar in some aspects, since the main indices of these markets have been quoted for a similar period of time and are among the largest stock markets in Central and Eastern Europe2. Second, the VSE and WSE have been competing markets in recent years. On the other hand, the FSE and VSE are developed markets, while the WSE is still an emerging market. Last but not least, Germany is the most important trading partner for both the Austrian and Polish economies.